ChemInform Abstract: Alkylation of 5‐(3‐Chlorobenzo[b]thien‐2‐yl)‐1, 2, 4‐triazole‐3‐thione with Epichlorhydrin and the Role of MW and Solid Support in the Reaction. Issue 41 (October 2015) - Rezki, Nadjet; Aouad, Mohamed Reda; Messali, Mouslim; El Ashry, El Sayed H.
Abstract An efficient eco‐friendly approach is developed for the selective synthesis of 2, 3‐ epoxypropylsulfanyltriazole (IV) by reaction of epoxy‐propane (II) with triazole‐3‐thione (I) under solvent‐free microwave conditions in the presence of a solid support.